The relationship between leader-member exchange and job satisfaction: The mediating role of work alienation - Siron R.B.; Muttar A.K.; Ahmad Z.A.; Tarsipan M.A.B. (Medwell Journals, 2023)
The aim of this study is to examine the relationship between leader-member exchange and job satisfaction among the academic stahh in the Iraqi technical colleges and institutes and evaluate the mediation effect of work alienation. A quantitative approach and survey instruments were adopted in this study. The total number of returned questionnaires was 419 from a total of 750 questionnaires. Structural Equation Modeling (SEM) was employeed to test the mediating effect of work alienation. The results revealed that work alienation partially mediated the relationship between leader-member exchange and academic job satisfaction among the academic staff ain Iraqi technical colleges and institutes. Medwell Journals, 2016.